ANALISIS KESALAHAN FONOLOGIS DALAM MEMBACA SURAT AL-FATIHAH DI PROGRAM TAHFIZH NURUL HUDA GARUT - Alwi Nizar Al-Ghifari; Lina Marlina (Al-Fakkaar, 2023)
This research was conducted with the aim of explaining the forms of phonological errors in reading Surah Al-Fatihah at the Nurul Huda Garut Tahfizh Program, as well as to identify the causes of phonological errors that occur in students at the institution, and the efforts that educators can make to address phonological errors made by students. In collecting data, the author used the observation method, writing method, and recording method. Additionally, the researcher also utilized observation and interview techniques in data collection. The research method employed in this study was qualitative descriptive research. The results of this study indicate that the phonological errors experienced by students in reading Surah Al-Fatihah include difficulties in pronouncing Arabic letters, such as the letter hamzah (Ø¡) being pronounced as 'ain (Ø¹) and the letter 'ain being pronounced as alif. These errors are overlooked by the Arabic language teacher. Furthermore, errors in vowel sounds Ù‰ÙŽØ§ (aa) and Ù‰ÙÙŠ (ii) were found in the recitation of Surah Al-Fatihah. The causes of these phonological errors include: (a) lack of attention from teachers, leading to students reading Surah Al-Fatihah incorrectly, and (b) lack of guidance regarding letter pronunciation and tajweed.